PEMBERDAYAAN KADER KESEHATAN MELALUI PROGRAM POSBINDU SEBAGAI UPAYA DETEKSI DINI PENYAKIT DAN PENCEGAHAN PENYAKIT TIDAK MENULAR (HIPERTENSI) DI WILAYAH KERKA PUSKESMAS SUKODONO KABUPATEN SIDOARJO - Sulystiono, Dony; Hotmaida Siagian; Muhammad Afif Hilmi Masyfahani (Health Community Engagement, 2025)
Hypertension is a disease with an increasing prevalence, especially in East Java Province, Indonesia. Despite the significant number of patients, only a small portion of them receive medical treatment. The Posbindu PTM (Integrated Non-Communicable Disease Post) program is used as a solution to early detect the risk factors of non-communicable diseases, especially hypertension. This program involves the role of health cadres to raise awareness and knowledge among the community. In its implementation, there are two main stages, namely the training on the 5 Posbindu PTM Tables technique and direct assistance in the Posbindu PTM activities within the community. The results show a significant increase in the cadres' knowledge after the training, with a significance level of 0.011 indicating the effectiveness of the training. Furthermore, the training was attended by 100% of the participants, demonstrating the active involvement of the health cadres. In the early detection process, 24 hypertension patients were identified, including 2 new cases, who directly received standard treatment from the local health center (Puskesmas). This step has had a positive impact on the 100% standard service coverage. The activities also resulted in two outputs, namely an article currently undergoing journal publication submission, and the establishment of 2 Posbindu PTM Work Groups in the Samangan Kulon village, each consisting of 5 health cadres. Through this program, it is hoped that the community will have a better understanding of hypertension and be able to prevent and manage their health conditions more effectively